Cobalt in mangrove snails, Nerita lineata and sediments from Peninsular Malaysia - Cheng, Wan Hee; Yap, Chee Kong; Ahmad, Zaharin Aris; Wong, Ling Shing; Ong, Ghim Hock (2016)
Rapid growth of the industries have generated various trace metal pollutions in the coastal waters of Peninsular Malaysia. Therefore it is essential to establish baseline studies of trace metal levels in marine species for biomonitoring purposes. This study aimed to provide the baseline concentration and the ability of the Nerita linaeta as a good biomonitoring agent for Co. Mangrove snails, N. lineata, and sediments were collected from at least 10 geographical sites of the western and southern part of Peninsular Malaysia from 2010 to 2011. The concentration of Co was determined in the shells, opercula and soft tissues of the N. lineata and the sediments by using ICPMS. The range of mean concentration of Co in the snail samples collected from Peninsular Malaysia were BDL – 0.96 µg/g dry weight, while the sediments range were 2.5 – 16.7 dry weight. The distribution of Co in the snails was in the decreasing order of soft tissues > opercula ≥ shell. The BSAF data and Person’s correlation coefficient between the sediments and the snails (shells, opercula and soft tissues) showed poor ability of the snail as a biomonitor for the Co.